GYMNASTICS HEALING IS IMPORTANT PART OF MEDICINE - Rabimkul Sultonov , Alisher Babaev , Abdukholik Bolbekov (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In this research paper describes the require for helpful works out in tumbling, which are pointed at treatment. too depicts the preferences and drawbacks of acrobatic in medication.